Application of the Number Head Together Learning Model to Improve Student Learning Achievement - Asmaul Khusna (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to improve the learning achievement of class XI IPA MAN 4 Madiun in Physics lessons through the Number Head Togather learning model. This research is a classroom action research consisting of 2 cycles. The data analyzed in this study were observation sheets and written test results. Data analysis techniques were carried out using quantitative description techniques. The success indicator of this research is that 75% of students complete the KKM. In the pre-cycle, 48.5% (16) of the students completed the KKM. In cycle I there were 75.2% (20) of students completing KKM. Then, in cycle II there were 87.9% (29) students who completed the KKM. The success of the research was obtained in cycle II. The Number Head Together learning model also succeeded in increasing student learning activities as evidenced by the success indicators of this research being included in the good category.